2019
DOI: 10.32479/ijeep.7747
|View full text |Cite
|
Sign up to set email alerts
|

Portfolio Diversification and Oil Price Shocks: A Sector Wide Analysis

Abstract: This paper investigates the time-varying relationship between the oil price and disaggregated stock market of India using dynamic conditional correlation multivariate GARCH and continuous wavelet transformation modelling approaches. Our findings reveal the evolving relationship between the oil price and disaggregated stock market. The correlations are generally volatile before the 2007-2008 crisis but since then the correlations are positive implying no diversification benefits for the investors during rising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The authors found that the exchange rate impacts the Firms negatively by having exposure to foreign sales. Ali and Khan (2019) studied the impact of oil prices on the Indian stock market using dynamic conditional correlation multivariate GARCH and wavelet transformation modelling approach. The author found that during 2007-2008, there was a negative correlation, but after the crisis, there was a positive correlation between the oil price and the exchange rate.…”
Section: Stock Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that the exchange rate impacts the Firms negatively by having exposure to foreign sales. Ali and Khan (2019) studied the impact of oil prices on the Indian stock market using dynamic conditional correlation multivariate GARCH and wavelet transformation modelling approach. The author found that during 2007-2008, there was a negative correlation, but after the crisis, there was a positive correlation between the oil price and the exchange rate.…”
Section: Stock Marketmentioning
confidence: 99%
“…Volatility spillover from oil prices to the stock market and exchange rate to the stock market and vice versa can also be observed across the studies. Volatility spillover has been studied in a large number of studies, particularly in the case of India and Vietnam (Ali et al, 2019;Drachal, 2018).…”
Section: Commonalitymentioning
confidence: 99%
“…Garg and Chauhan (2012) found that the Indian sectors such as auto, metal, banking, health care, technology, and real estate are highly related to the US and other developed markets. Ali et al (2019) reported reduced diversification in the Indian disaggregated stock market during the oil price movement. From the perspective of China (Cao et al, 2013) noticed a strong correlation between sectoral indices during market ups and down conditions, otherwise, it was lower.…”
Section: Literature Reviewmentioning
confidence: 99%